2018
DOI: 10.1007/s00330-018-5611-z
|View full text |Cite
|
Sign up to set email alerts
|

Observed changes in brown, white, hepatic and pancreatic fat after bariatric surgery: Evaluation with MRI

Abstract: • No significant changes were observed in fat-fraction, T2* and volume of brown adipose tissue after bariatric surgery. • Non-alcoholic fatty liver disease was resolved after surgery. • Abdominal white fat and liver fat were significantly reduced 6 months after surgery and become stable between 6 and 12 months while pancreatic fat was significantly reduced between 0 and 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The MRI acquisition for abdominal subcutaneous and visceral adipose tissue measurements was performed from the dome of the diaphragm to the pubic symphysis. The authors found that within 12 months after surgery, subcutaneous adipose tissue volume decreased by 34.5% and visceral adipose tissue volume by 51.2%, mostly in the first 6 months following surgery [25]. The study using whole-body MRI showed that relative loss was significantly higher for visceral than for subcutaneous adipose tissue (52.3 vs. 42.3%) 12 months following bariatric surgery [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MRI acquisition for abdominal subcutaneous and visceral adipose tissue measurements was performed from the dome of the diaphragm to the pubic symphysis. The authors found that within 12 months after surgery, subcutaneous adipose tissue volume decreased by 34.5% and visceral adipose tissue volume by 51.2%, mostly in the first 6 months following surgery [25]. The study using whole-body MRI showed that relative loss was significantly higher for visceral than for subcutaneous adipose tissue (52.3 vs. 42.3%) 12 months following bariatric surgery [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies a higher relative reduction of visceral fat as compared to other compartments was observed [23][24][25][26]. The authors of Swedish study examined body composition of 166 women before and 2 years after RYGB.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent research (Abe et al, ) indicated that the percentage of the fat fraction in subcutaneous adipose tissue was 87.1% in nonobese adults (BMI range 21.7‐24.6 kg/m 2 ). In severely obese patients (BMI 35 kg/m 2 ), a study reported that fat fraction percentage of subcutaneous adipose tissue was 84.4% (range 82.3‐85.7%) (Hui et al, ). There are only a few studies regarding the fat fraction percentage separated by sex and the results were inconsistent; one study observed a significant difference between men and women (Jones et al, ), but another did not (Hui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations of the underlying mechanisms to the association between BAT and 2h glucose in adolescents are warranted. Also, changes in sBAT FF and T2* before and after intervention, eg, bariatric surgery as recently studied, are potential topics for forthcoming studies.…”
Section: Discussionmentioning
confidence: 99%